2013
DOI: 10.1111/bph.12183
|View full text |Cite
|
Sign up to set email alerts
|

Targeting survival pathways in chronic myeloid leukaemia stem cells

Abstract: leukaemia (CML) is a clonal myeloproliferative disorder characterized by the presence of a fusion oncogene BCR-ABL, which encodes a protein with constitutive TK activity. The implementation of tyrosine kinase inhibitors (TKIs) marked a major advance in CML therapy; however, there are problems with current treatment. For example, relapse occurs when these drugs are discontinued in the majority of patients who have achieved a complete molecular response on TKI and these agents are less effective in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 128 publications
0
55
0
Order By: Relevance
“…However, abolition of LSCs that give rise to disease persistence would be beneficial in the majority of patients and will most likely require an alternative, non-TKI approach to treatment. A number of intracellular signaling pathways and molecules have been identified that are potentially involved in LSC survival and these are being investigated as potential therapeutic targets [124,125]. The role of the bone marrow microenvironment in protecting LSCs is also under scrutiny [126,127].…”
Section: Options For Patients Who Respond Well To First-line Therapymentioning
confidence: 99%
“…However, abolition of LSCs that give rise to disease persistence would be beneficial in the majority of patients and will most likely require an alternative, non-TKI approach to treatment. A number of intracellular signaling pathways and molecules have been identified that are potentially involved in LSC survival and these are being investigated as potential therapeutic targets [124,125]. The role of the bone marrow microenvironment in protecting LSCs is also under scrutiny [126,127].…”
Section: Options For Patients Who Respond Well To First-line Therapymentioning
confidence: 99%
“…Despite the dramatic clinical progress upon treatment with these drugs and the possibility to discontinue treatment in approximately 50% of patients (14), allogeneic stem cell transplantation represents the only proven long-term curative treatment (15)(16)(17). Therefore, novel therapeutic strategies are warranted to target persisting stem cells and resistant clones alone or in combination with BCR-ABL TKI.…”
Section: Introductionmentioning
confidence: 99%
“…Other pathways and mediators have been implicated in LSC/HSC survival, such as Akt phosphatidylinositol-3 kinase (PI3K) [20], NOTCH signalling [18], and the Wnt/β-catenin pathway [21]. It is possible to target these pathways, by inhibiting for example the activation of Akt using PI3K inhibitors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is possible to target these pathways, by inhibiting for example the activation of Akt using PI3K inhibitors. Sinclair and colleagues [21] provide a detailed overview of the various survival pathways in CML stem cells, in addition to discussing methods to target these pathways.…”
Section: Accepted Manuscriptmentioning
confidence: 99%